Generating Micro, Small and Medium Enterprises in a Pandemic Period with Innovation and Technology - Hamdani; Eneng Wiliana; Nining Purnaningsih; Dhea Zatira; Khorida AR (EQUATOR SINAR AKADEMIA, 2022)
The seminar